Pattern of antimicrobial usage for prophylaxis of surgical site infection in a tertiary care hospital of Western Uttar Pradesh - Kesar, Parul; Gupta, Surabhi; Bhalla, H. L.; Panday, Anita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The practice of giving antibiotic prophylaxis has resulted in the reduction of surgical site infections (SSI), thus reducing cost, morbidity, and mortality. Common nosocomial infections in surgical patients include SSIs, urinary tract infections (UTIs), pneumonias and blood stream infections (BSIs). The present study was, therefore, designed to analyze the efficacy of antimicrobials used for prophylaxis during surgery in a tertiary care hospital in India. Methods: Total 100 patients were enrolled. Name, timing, route, dose of antimicrobials given were recorded. All the relevant data was taken from the patient’s medication charts and medical records. Chi-square test and t-test were applied. Results: The optimal time of giving antimicrobial prophylaxis in present study was 1 hour before the surgery. A total of 8 different antimicrobials were prescribed to 100 patients, out of which most commonly prescribed were cephalosporin i.e. 82%. Majority of SSI (57.12%) occurred when the duration of surgical antimicrobial prophylaxis (SAP) was for ≥2 hours (p value <0.05). Common organisms seen in SSI were E. coli, S. aureus, Pseudomonas and Kleibsella species. The hospital stay of patients with SSI was more as compared to patients without SSI in present study (p value <0.05). Conclusions: It has been observed that inappropriate selection and timing of giving SAP play an important role in developing SSI, which can be adequately controlled by adopting SAP guidelines, good infection control practices and risk factor analysis.